2021
DOI: 10.3389/fphar.2021.670158
|View full text |Cite
|
Sign up to set email alerts
|

The Depolarization-Evoked, Ca2+-Dependent Release of Exosomes From Mouse Cortical Nerve Endings: New Insights Into Synaptic Transmission

Abstract: Whether exosomes can be actively released from presynaptic nerve terminals is a matter of debate. To address the point, mouse cortical synaptosomes were incubated under basal and depolarizing (25 mM KCl-enriched medium) conditions, and extracellular vesicles were isolated from the synaptosomal supernatants to be characterized by dynamic light scattering, transmission electron microscopy, Western blot, and flow cytometry analyses. The structural and biochemical analysis unveiled that supernatants contain vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The Ca 2+ playes an important role in regulating the exosome secretion from MVBs (Butreddy et al., 2021; Gurunathan et al., 2021; Olivero et al., 2021,). To assess whether the LPS induced exosome release was associated with the change in intracellular Ca 2+ , we measured whether LPS can modify the intracellular Ca 2+ concentration ([Ca 2+ ] i ) of EPC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ca 2+ playes an important role in regulating the exosome secretion from MVBs (Butreddy et al., 2021; Gurunathan et al., 2021; Olivero et al., 2021,). To assess whether the LPS induced exosome release was associated with the change in intracellular Ca 2+ , we measured whether LPS can modify the intracellular Ca 2+ concentration ([Ca 2+ ] i ) of EPC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has indicated that Ca 2+ is a key participant in the process of exosome release (Butreddy et al., 2021; Gurunathan et al., 2021; Olivero et al., 2021). The Ca 2+ may play a role as a messenger in the activation of exosome‐carrying cells to release these small vesicles at the proper site and time.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the binding free energies calculated by carrying out the MM/GBSA method, known to be one of the rigorous and efficient methods to predict relative binding affinities, has been useful for evaluating the strength of EA’s affinity over the α 2 -ARs binding pocket [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. In this way, 1000 snapshots from 50 ns of MDs are extracted for the binding free energy calculations of both the α 2 -ARs-EA complex and the known partial agonist and antagonist in complex to α 2 -ARs [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Synaptosomes are pinched-off nerve terminals that contain structures (e.g., vesicles, mitochondria, endoplasmic reticulum, synthetic and enzymatic pathways, see Olivero et al, 2021 [ 52 ]) that are present in the neuronal processes they originate from, confirming their presynaptic origins. Synaptosomes can take up, synthesize, metabolize, store, and release transmitters, and possess naïve receptors and transporters, whose activation controls the synaptosomal functions, particularly transmitter exocytosis.…”
Section: Methodsmentioning
confidence: 99%
“…Ca 2+ handling abnormity promotes the secretion of exosomes has been reported earlier. Olivero et al found that the depolarization-evoked release of exosomes from cortical synaptosomes occurred in a Ca 2+ -dependent fashion [20] . Interestingly, physical stimuli such as high frequency acoustic stimulation also leads to calcium-dependent exosomes release [21] .…”
Section: Discussionmentioning
confidence: 99%